L’impact des changements climatiques sur les rendements des principales cultures céréalières au Sénégal - Faye, Adama; Ndiaye, Malick; Ndiaye, Abdoulaye (DEMO, 2018)
This article estimates the impact of climate change on the yields of the main cereal crops in Senegal. We used a linear correlation coefficients analysis and multivariate regression for our empirical investigation. Our results show that temperature and precipitation levels have a positive influence on cereal yields in Senegal. However, the economic effect of the variation of the temperatures is more important than of the variation of the precipitation on the cereal yield products. In Senegal, the low level of temperatures would explain a good part of the low yields in the cereals sector. Average temperatures are still below 290C, which does not boost productivity in the cereals sector. These results imply important economic policy measures in the sector.(original abstract)